Divides, High Rise and Boundaries: A Study of Toronto's Downtown East Side Neighbourhood - Fumia, Doreen (Ethnologies, 2010)
Acts of domination are not always easy to identify, and in hindsight, the best intentions of post WWII rezoning and “arden city”high-rise developments have not served poor, racialized immigrants well. While the poor in the Downtown East Side of Toronto did not benefit from postwar urban renewal, the middle classes did, but only because they mustered resources in order to block zoning that would allow high rises. As a result, one area of the DTES is one of the most condensed stocks of beautifully preserved Victorian-style homes in Canada. This article interrogates the postwar rationalization of the DTES and the claim, and the resistance to it, that it is “ot the right for 3000 poor people to live downtown”.